Study in relationship between perceived stress and academic performance of students in the faculty of earth sciences, Universiti Malaysia Kelantan Kampus Jeli - Ain Syuhada Afifah Hamzah (2014)
Numerous studies found that stress influences the overall academic performance of the students because nowadays most of the institutions place higher demand for the better achievements. The number of universities in Malaysia has increased for the past few years. Due to the increasing number of universities, students may face more conflicts in their studies as the university managements are facing a competitive pressure from other universities. Hence, the aim of his study was to determine the relationship between level of perceived stress and students' academic performance. This study involved 228 students selected from three courses in the Faculty of Earth Sciences, Universiti Malaysia Kelantan Kampus Jeli. A set of questionnaire consisting of three main sections; Demographic profile, Perceived Stress and Stress Factors, was used to investigate how perceived stress were related to students' academic performance. The results of the Pearson Correlation test showed that there is a positive and strong relationship between the perceived stress scale (PSS) and the students' academic performance. The study confirmed and supported the fact that perceived stress was significantly and strongly related to students' academic performance.